2013
DOI: 10.1371/journal.pone.0075246
|View full text |Cite
|
Sign up to set email alerts
|

Mice Infected with Low-Virulence Strains of Toxoplasma gondii Lose Their Innate Aversion to Cat Urine, Even after Extensive Parasite Clearance

Abstract: Toxoplasma gondii chronic infection in rodent secondary hosts has been reported to lead to a loss of innate, hard-wired fear toward cats, its primary host. However the generality of this response across T. gondii strains and the underlying mechanism for this pathogen-mediated behavioral change remain unknown. To begin exploring these questions, we evaluated the effects of infection with two previously uninvestigated isolates from the three major North American clonal lineages of T. gondii, Type III and an atte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
110
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 36 publications
5
110
0
4
Order By: Relevance
“…Since chronic infection leads to activated microglia around many, but not all, tissue cysts (47), a potential cause of signaling and behavioral abnormalities would be inflammation. Interestingly, it was discovered that mice infected by attenuated parasites incapable of persisting as cysts in the brain still exhibited attraction to cat odor months after acute infection had been completely cleared and parasites were no longer detectable in the brain by PCR (13). These findings suggest that alteration or rewiring of the mouse brain during acute infection leads to alterations in rodent behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since chronic infection leads to activated microglia around many, but not all, tissue cysts (47), a potential cause of signaling and behavioral abnormalities would be inflammation. Interestingly, it was discovered that mice infected by attenuated parasites incapable of persisting as cysts in the brain still exhibited attraction to cat odor months after acute infection had been completely cleared and parasites were no longer detectable in the brain by PCR (13). These findings suggest that alteration or rewiring of the mouse brain during acute infection leads to alterations in rodent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents that become infected by T. gondii exhibit an unusual behavioral response: they lose their instinctive aversion to the odor of cats and instead become mildly attracted to the scent (5)(6)(7)(8)(9)(10)(11)(12)(13). This behavioral manipulation appears specific to the cat (7,8), and it has been speculated that this facilitates transmission (9).…”
mentioning
confidence: 99%
“…Interestingly, T. gondii infection increases the risk of schizophrenia roughly 2.7 times, which is higher than that for genes associated with schizophrenia (5). Several studies have also suggested that rodents infected with T. gondii exhibit decreased avoidance behavior in response to cat odors, indicating manipulation of the host's behavior by T. gondii to facilitate the parasite's transmission and complete sexual replication in the definitive host (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…For example, Toxoplasma gondii alters the behavior of rodents up to eliminating the instinct of self-preservation while maintaining newly acquired psychic qualities after full recovery. [3] In the available literature, we have not found works about the genetic fixation of the new mental properties in rodents that underwent toxoplasmosis. It was noted that there is a similarity in some syndromic forms of schizophrenia and toxoplasmosis in humans, [4] as well as a significant correlation between toxoplasmosis and expressed anxiety.…”
mentioning
confidence: 99%